A rare isolated herbicide scrotal burns: A case report - Mahamudu Ayamba Ali; Redwan Musah; Mawuenyo Attawa Oyortey; Marian Esi Ashong; Felicia Nyarko (Elsevier, 2022)
Introduction: Paraquat-exposed scrotal burns as farming hazard is rare. Such scrotal burns may mimic fourniers gangrene and increase management challenges when the presentation is delayed. With the increasing use of herbicides among farmers who may lack access to agriculture extension services' safety advice and prescribed protective farm wear, the risk of frequent herbicide scrotal burns may be higher than reported. Case presentation: A 24-year-old man presented with painful scrotal swellings 3 days after exposure to paraforce herbicide. Physical examination revealed multiple bullous lesions and ulcers on the scrotum which mimic Fourniers gangrene. Immediate management aimed to prevent Fournier's gangrene and testicular damage was successful. Conclusion: Conservative treatment for paraquart scrotal burns may be sufficient even in late presentation. Inspect spraying machine and protective wear before use.